The Effect Of Work Family Conflict On Turnover Intention Through Organizational Commitment As An Intervening Variable: Study on Employees of PT. Titipan Kilat Surabaya - Sabella, Selly Amita; Fazlurrahman, Hujjatullah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to examine and analyze the effect of work-family conflict on turnover intention through organizational commitment to employees of PT. Titipan Kilat Surabaya. This research is a type of quantitative research. The sampling technique used disproportionate stratified random sampling with a sample of 135 respondents. Statistical analysis in this study used SEM (Structural Equation Modeling) with SmartPLS 3.2.9 software. The results of the study prove that work-family conflict has a positive and significant effect on turnover intention. Work-family conflict has a negative and significant effect on organizational commitment. Organizational commitment has a negative and significant effect on turnover intention. Organizational commitment is able to mediate between work-family conflict and turnover intention.